2005
DOI: 10.1161/circulationaha.104.492017
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Thrombus on Atrial Septal Defect Closure Device as a Source of Cerebral Emboli 3 Years After Implantation

Abstract: A 55-year-old man presented with sudden occurrence of recurrent transitoric ischemic attacks with dysphasia and paresis of the left side in May 2004. Other than these symptoms, he presented in good physical condition, with no cyanosis or edema, and his ECG showed regular sinus rhythm at normal rate. Chest x-ray and laboratory studies were unremarkable. He was not taking medication.His medical history consisted of a patent foramen ovale (PFO) that had been closed 3 years earlier with the CardioSeal/Starflex Occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Although thrombus disappeared or markedly diminished after additional anticoagulation therapy in three patients, one patient had surgical explantation of the device due to progressive increase in the size of thrombus with hypermobility despite intensive anticoagulation therapy 12 . Finally, in a recent case report, Ruge et al report a left atrial thrombus on a Starflex device 3 years after implantation 13 . In the CLOSEUP study, where transesophageal echocardiograms were performed that included a detailed examination of the left atrial anchor for evidence of thrombus, no patients were found to have device related thrombus at any time.…”
Section: Discussionmentioning
confidence: 99%
“…Although thrombus disappeared or markedly diminished after additional anticoagulation therapy in three patients, one patient had surgical explantation of the device due to progressive increase in the size of thrombus with hypermobility despite intensive anticoagulation therapy 12 . Finally, in a recent case report, Ruge et al report a left atrial thrombus on a Starflex device 3 years after implantation 13 . In the CLOSEUP study, where transesophageal echocardiograms were performed that included a detailed examination of the left atrial anchor for evidence of thrombus, no patients were found to have device related thrombus at any time.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the benefits of these devices, there remains the potential disadvantage of large foreign material in the atria. Potential complications associated with PFO implant devices include thrombus formation [18–20], device erosion [21–23], and atrial fibrillation [24–26]. Another disadvantage seems to be that these devices may obstruct transeptal access to the left atrium and preclude the treatment of acquired heart disease such as percutaneous heart valve repair and replacement, left atrial appendage closure, and arrhythmia intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Complications include device embolisation, cardiac perforation, device thrombus, stroke, arrhythmia and serious vascular injury. These types of complication, together with device failure, may require conversion to open surgery either immediately, or at a later date 59. Recent data suggest that late valve problems may also occur 10.…”
Section: Transcatheter Closure Of Secundum Asd: the Risksmentioning
confidence: 99%